"1‐2‐3 Pap" Intervention Improves HPV Vaccine Series Completion Among Appalachian Women. (10th January 2013) - Vanderpool, Robin C.; Cohen, Elisia L.; Crosby, Richard A.; Jones, Maudella G.; Bates, Wallace; Casey, Baretta R.; Collins, Tom
<x xml:space="preserve">Abstract</x> Completion of the Human Papillomavirus (HPV) vaccine series is a national priority. This study not only identified correlates of intent to complete the vaccine series and actual series completion, but also tested the efficacy of a DVD intervention to promote series completion. Women's beliefs that all 3 doses reduced cancer risk predicted intent and completion. Intention predicted completion, as did the belief that having a friend accompany the woman would promote completion. Beyond these effects, women assigned to the intervention were 2.44 times more likely than women in the usual care group to complete the series. Thus, in controlled analyses, a theory‐grounded DVD intervention successfully promoted HPV series completion in a community setting. This method of intervention has high translational potential.